Assessment of the Quality of Antenatal Care Rendered at a Northern Nigeria Primary Health Care Center, Zaria, Nigeria - NH, Madugu; M A, Abdul; k, Sabitu; M, Mandara; U, Bawa (International Journal of Medical and Health Sciences Research, 2017)
Background: Primary health care facilities are the closest to the community and are easily accessible to pregnant women and their children. Ensuring quality Antenatal care by skilled attendants at this level is pre-requisite to reducing pregnancy complications and over all maternal mortality Objective: This study was aimed at assessing the adequacy of antenatal care rendered at this level of care. Methods: A cross sectional study was conducted at Babban-dodo primary health center, Zaria. An exit Questionnaires was administered to 400 pregnant women. Information on their demographic status and information about the Antenatal care just received was obtained focusing standard protocol for antenatal care. Result: showed that the women were not rendered all the full component of ANC. History of feeling unwell was not asked in 88%, examination including blood pressure check was done in only 37%, Obstetrics examination was done in more 80% of the women however symphsio-fundal height was not measured with tape. The women were sent to do most of the routine investigations, as they pay for these investigations and the revenue collected is used to partially run the hospital. There was only one nurse midwife at the center; community health workers were the sole providers and no medical doctor visit the hospital. Ninety six percent of the respondents were satisfied with the services while 3.6% were dissatisfied. Conclusion: There is total disregard for standard of care for antenatal services expected at this level. There is the need for re-assessment of all primary health care centers that are the first point of contact with our pregnant women, if reducing maternal mortality rate is great concern to all of us.